LA FORMA NARRATIVA EN LA MALA EDUCACIÓN (PEDRO ALMODÓVAR, 2004) - Pedro Poyato Sánchez, (Fonseca, Journal of Communication, 2023)
One of the features which characterizes Almodovar’s last drama is, undoubtedly,the narrative form. The way in which events are ordered, playing with chronological time, results in intricate narrative labyrinths due to the variety of voices narrating those events. The aim of this work is to analyze the narrative form in Bad Education, from the point of view of how those voices and the different temporal layers displayed in the film are combined.